Regional Economic Outlook, October 2013, Sub-Saharan Africa : Keeping the Pace. (Regional Economic Outlook, 2013)
The October 2013 Regional Economic Outlook: Sub-Saharan Africa provides a comprehensive report on the prospects for growth in the region, as well as the major risks to the outlook. Generally, growth is expected to remain strong despite a downward revision since the May 2013 report. The report analyzes drivers of growth in nonresource-rich sub-Saharan African countries, and examines the risks to frontier market economies of volatile capital flows as they become more integrated with international capital markets.